Brazil-Africa relations : historical dimensions and contemporary engagements, from the 1960s to the present - Seibert, Gerhard, 1954-; Vizentini, Paulo Gilberto Fagundes, 1955- (James Currey, 2019)
When Lula da Silva became President of Brazil in 2003 he declared Africa a priority of his country's ambitious global foreign policy. Since then, Brazil has become one of the key emergent powers in Africa by strengthening political ties and trade with the continent. While, due to a worsening economy, the Dilma and Temer presidencies have other political priorities, strong links with the continent continue to exist. The authors trace the long history of Brazil-Africa relations from the early 16th century and the slave trade, through their decline during European colonialism, their resurgence following many African countries' independence, fluctuations during Brazil's military rule in the 1960s and '70s, to the expansion of its interests under Lula and the first years under Dilma. Taking a broad range of perspectives, they examine: the way in which the rights of those of African descent have become increasingly recognized without having brought racial equality; the strengthening links of Brazilian Pentecostal Churches; the growth of South-South cooperation; and Brazil-Africa relations in the South Atlantic context. The final chapter looks at the wider implications of the present political and economic crises for Brazil's future foreign policy in Africa, and the impact of the new leadership in late 2018.